Культурні особливості історико-етнографічних регіонів України - Томачинська, В. С.; Корсун, Д. М. (ХНУРЕ, 2019)
The author gave short information about the culture and the ethnographic distribution of Ukraine. Urbanization didn’t destroy the ethnographic peculiarities a lot of regions, but changed the way of life and conditions of ethnos.